O conceito de amor em Hannah Arendt: da perspectiva agostiniana ao amor mundi - Oliveira, Elciene Alves Ferreira de (Universidade do Vale do Rio dos Sinos, 2023)
In this paper the concept of love in Hannah Arendt is discussed: from the Augustinian perspective to "amor mundi", investigating the presence of this theme from her first writing: "The Concept of love in Saint Augustinian”, moving on to other writings such as: "The Human Condition" and "Origins of Totalitarianism"; and, Augustine's writings like "Confessions". In addition, comments on these writings regarding the proposition of the theme, its developments and relevance, were analyzed. In addition, an analysis of three forms of love as an expression of love for the world and how they are reflected in the writings was carried out, verifying how the author qualifies the concept of love, in the context of Augustinian philosophy, resizing it to a new form to love: “amor mundi”. We analyzed these three forms of love: love as desire, in the reach of perennial good, insecure; love of neighbor, turned to God, to others and to oneself and; amor caritas, higher and turned towards the Eternal, incorruptible. In the latter, the perspective of a world that becomes a space for all connections in the promotion of social and political ethics is discussed, under the responsibility of getting involved with the other, with oneself and with one's surroundings. Still, love in socio-political relationships was discussed, conceiving a world that can be re-signified in the context of the public sphere, seeking to emphasize the value of recognition, reconciliation and forgiveness. When analyzing the work "Origins of Totalitarianism", we emphasize that in the context of anti-Semitism, imperialism and totalitarianism, there are no perspectives of care for the world, as a space for everyone resulting from a political action of understanding, respect and responsibility for the common space to all men. In "The Human Condition”, “amor mundi” in vita activa was discussed, presenting the world in three dimensions: the natural space of the work, as a human artifice through the work and, as an apparent world, through the political action of men. As for the results achieved in this research, it was verified, in the work of Hannah Arendt, influences of the Augustinian philosophy and the presence of the conception of “amor mundi” as responsibility for the world.
Keywords: Arendt; Agostinho; Amor; Reconciliação; Mundo; Augustine; Love; Reconciliation; World; ACCNPQ::Ciências Humanas::Filosofia